Recent Advances in Neuromyelitis Optica Spectrum Disorder: Pathogenesis, Mechanisms and Potential Treatments - Du, Yi; Li, Kaijun; Liu, Wei; Song, Ruitong; Luo, Meifeng; He, Jianfeng; Xu, Xiaoyu; Qu, Xiaosheng (Current pharmaceutical design, 2022)
Neuromyelitis optica spectrum disorder (NMOSD) is an acute or subacute demyelinating disease that affects mainly the optic nerve and spinal cord. A major proportion of NMOSD cases have a relationship with autoimmunity to aquaporin 4 (AQP4) found on the central nervous system. NMOSD can occur repeatedly, causing symptoms such as decreased vision and weakness of limbs. The main goal of the current therapy is to relieve acute symptoms and prevent recurrence of the disease. Without timely and appropriate treatment, the recurrence and disability rates are high. In the present work, we review recent advances in the diagnosis and treatment of patients with NMOSD, as well as the pathogenesis and mechanisms of AQP4-IgG-seropositive NMOSD.